Next-generation spin-0 dark matter models - Abe, Tomohiro; Bauer, Martin; Brandt, Oleg; Henkelmann, Lars (Arxiv, 2018)
Dark matter (DM) simplified models are by now commonly used by the ATLAS and CMS Collaborations to interpret searches for missing transverse energy ($E_T^miss$). The coherent use of these models sharpened the LHC DM search program, especially in the presentation of its results and their comparison to DM direct-detection (DD) and indirect-detection (ID) experiments. However, the community has been aware of the limitations of the DM simplified models, in particular the lack of theoretical consistency of some of them and their restricted phenomenology leading to the relevance of only a small subset of $E_T^miss$ signatures. This document from the LHC Dark Matter Working Group identifies an example of a next-generation DM model, called $2HDM+a$, that provides the simplest theoretically consistent extension of the DM pseudoscalar simplified model. A comprehensive study of the phenomenology of the $2HDM+a$ model is presented, including a discussion of the rich and intricate pattern of mono-$X$ signatures and the relevance of other DM as well as non-DM experiments. Based on our discussions, a set of recommended scans are proposed to explore the parameter space of the $2HDM+a$ model through LHC searches. The exclusion limits obtained from the proposed scans can be consistently compared to the constraints on the $2HDM+a$ model that derive from DD, ID and the DM relic density.
CERN-LPCC-2018-02
Gesehen am 21.01.2019